Identification and synthesis of end-of-life decision-making measures: a scoping review - Bucko, Patricia; Novack, Miriam A.; Ho, Emily H.; Ece, Berivan; Burleigh, Evan; Mather, Molly A.; Karpouzian-Rogers, Tatiana; Dworak, Elizabeth M.; Pila, Sarah; Hosseinian, Zahra; Han, S. Duke; Lichtenberg, Peter A.; et al. (Frontiers in Medicine, 2025)
BackgroundCognitive impairment (CI) and related conditions are known to affect decision-making (DM), particularly in older adult populations. The intersection of CI and DM ability is crucial in end-of-life (EoL) care, where there is a confluence of heterogenous preferences and values often across different constituents (e.g., healthcare providers, family members, and proxies). Standardized questionnaires are necessary to characterize patients’ EoL decisions, preferences, and readiness, but the extent of available measures is widely unknown.ObjectiveThis scoping review aims to summarize the current state of the literature regarding EoL decision-making measures. This effort supports the development of the Advancing Reliable Measurement in Cognitive Aging and Decision-making Ability (ARMCADA) research initiative, which seeks to develop a decision-making battery for use in older adults.MethodsFollowing the Arksey and O’Malley framework, we conducted a scoping review for multiple domains of DM in studies published between January 2018 and November 2023. Any paper that assessed or characterized DM in participants 45 years and older was extracted for the DM domain, population characteristics, and DM measures.ResultsAn initial search identified 16,286 articles, of which 705 were classified as assessing DM. Of those, 34 articles included measures of the EoL domain, and 28 unique measures were identified. The MacArthur Competence Assessment Tool for Treatment (MacCAT-T), the Decisional Conflict Scale (DCS), and the Decision Regret Scale (DRS) were the only assessments used more than once in the scoping review. Many studies assessed clinical populations, including those with CI/dementia (12%), cancer (24%), and chronic conditions (16%). Findings show that measures used at the end of life emphasize decisional preferences, efficacy, and conflict.ConclusionOverall, this review highlights the lack of DM ability measures that can assess older adults’ capacity to make decisions regarding EoL-specific issues (e.g., life-sustaining treatment and pain management).